Impact of the European Union Regulations on Indonesian Oil Palm Smallholder Farmers - Hasan, Mohamad Fadhil; Fadhil, Ilma; Fahmid, Mirah M.; Ahmad, Tauhid (International Journal of Oil Palm, 2022)
In 2020 Indonesian smallholder farmers produced around 35 % of the total palm oil production, the most traded vegetable oil. Smallholders play an essential role in developing country economies – most strikingly due to their success at reducing poverty and improving social benefits. The cultivation of palm oil has proven benefits for the smallholders themselves and the local community. However, oil palm smallholders are at risk of being cut out of global supply chains by European union (EU) regulations. The EU’s discrimination against palm oil smallholders is wide-ranging, including the EU Renewable Energy Directive II and the forthcoming Due Diligence Regulation imposing restrictions designed to undermine Indonesian palm oil in the global marketplace. This paper elaborates on how palm oil smallholders contribute to desirable economic and social goals and how the approach of the EU is deliberately undermining those goals.